2003
DOI: 10.1159/000070179
|View full text |Cite
|
Sign up to set email alerts
|

The <i>Alu</i>I Calcitonin Receptor Gene Polymorphism (TT) Is Associated with Low Bone Mineral Density and Susceptibility to Osteoporosis in Postmenopausal Women

Abstract: Osteoporosis is a common disorder with a strong genetic component. Our aim was to evaluate the correlation of theAluI calcitonin receptor gene polymorphism to bone mineral density and their relationship to osteoporosis. We determined the AluI calcitonin receptor gene polymorphism using polymerase chain reaction-based restriction analysis in 167 postmenopausal women in Taiwan. The polymorphism was detected by the restriction enzyme AluI, where the C allele indicated the absence of the cuttable site and the T al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…The three most significant changes in gene expression that were based on dietary P deficiency and its interaction with genetic background were seen in CALCR, VDR and IGFBP3. Polymorphisms in the human CALCR gene and VDR gene have been shown to be associated with BMD [53][54][55][56][57][58]. Based on the expression data, CALCR, VDR and IGFBP3 are good candidates for single nucleotide polymorphism studies.…”
Section: Discussionmentioning
confidence: 99%
“…The three most significant changes in gene expression that were based on dietary P deficiency and its interaction with genetic background were seen in CALCR, VDR and IGFBP3. Polymorphisms in the human CALCR gene and VDR gene have been shown to be associated with BMD [53][54][55][56][57][58]. Based on the expression data, CALCR, VDR and IGFBP3 are good candidates for single nucleotide polymorphism studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report an association between the CTR polymorphism Alu I and lumbar spine and femoral neck BMD in both men and women, but the reports have been somewhat contradictory. Studies in postmenopausal women revealed that the CC genotype is more common in non-osteoporotic women than the TT genotype [30,31], and that the TT genotype is associated with lower lumbar spine and femoral neck BMD and increases the predisposition for osteoporosis [32,33]. The opposite finding was suggested by Braga et al [34] who reported that the CC genotype is associated with decreased BMD and is more common in men with hip or vertebral fractures than in control subjects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present data supported the protective effect of this allele on the risk factor of osteoporosis according to nutritional condition. There are many reports on the association between this polymorphism and BMD or osteoporosis in mainly postmenopausal women with inconsistent results [3,7,[17][18][19][20][21][22][23] . Because this polymorphism is located within the fourth intracellular domain of CTR [6] , and plays an important role in the binding of CT, the significant association between this polymorphism and some bone phenotypes in our study may reflect the functional role such as ligand binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype Analysis of CTR AluI RFLP Genomic DNA was prepared from buffy coats from blood (5 ml) and then was screened for the CTR Alu I polymorphism using PCR reaction, followed by Alu I digestion, according to a previously published protocol [7] .…”
Section: Measurement Of Bone Parametersmentioning
confidence: 99%
See 1 more Smart Citation